What about the dentist–patient relationship in dental tourism?. Issue 3 (30th April 2013) - Conti, Adelaide; Delbon, Paola; Laffranchi, Laura; Paganelli, Corrado
Abstract : Dental tourism is patients travelling across international borders with the intention of receiving dental care. It is a growing phenomenon that raises many ethical issues, particularly regarding the dentist–patient relationship. We discuss various issues related to this phenomenon, including patient autonomy over practitioner choice, patient safety, continuity of care, informed consent and doctor–patient communication, among other factors. In particular, patients partaking in medical tourism should be informed of its potential problems and the importance of proper planning and post-treatment care to guarantee high-quality treatment outcomes.